2015
DOI: 10.4172/2329-6488.s1-001
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Volume in Offspring from Multiplex for Alcohol Dependence Families: The Moderating Influence of Childhood Environment and 5-HTTLPR Variation

Abstract: Background The increased susceptibility for developing alcohol dependence seen in offspring from families with alcohol dependence may be related to structural and functional differences in brain circuits that influence emotional processing. Early childhood environment, genetic variation in the serotonin transporter-linked polymorphic region (5-HTTLPR) of the SLCA4 gene and allelic variation in the Brain Derived Neurotrophic Factor (BDNF) gene have each been reported to be related to volumetric differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 78 publications
0
10
1
Order By: Relevance
“…Hill’s group has found that the offspring of alcoholic relatives had lower [right > left] asymmetry ratios of combined gray and white orbital volume, and that orbital white matter asymmetry in these offspring correlated with greater impulsivity (Hill et al, 2009). The same group (Hill et al, 2001, 2013) and Dager et al (2015) also detected loss of right amygdala volume in the adolescent offspring of families with alcoholism. Most recently, Cservenka et al (2015) reported that family history density was related to left nucleus accumbens volume in adolescents, although only in girls.…”
Section: Discussionmentioning
confidence: 67%
“…Hill’s group has found that the offspring of alcoholic relatives had lower [right > left] asymmetry ratios of combined gray and white orbital volume, and that orbital white matter asymmetry in these offspring correlated with greater impulsivity (Hill et al, 2009). The same group (Hill et al, 2001, 2013) and Dager et al (2015) also detected loss of right amygdala volume in the adolescent offspring of families with alcoholism. Most recently, Cservenka et al (2015) reported that family history density was related to left nucleus accumbens volume in adolescents, although only in girls.…”
Section: Discussionmentioning
confidence: 67%
“…One of the most well-replicated neuroimaging findings in FHP individuals is abnormal amygdala volume. Several studies have found that FHP individuals have smaller amygdala than FHN individuals, 9,53 whereas other studies found this difference only in the right amygdala. 15,54 Smaller amygdala have been detected as early as childhood 54 and persist after matching for IQ and socioeconomic status.…”
Section: Introductionmentioning
confidence: 90%
“…HR children who carry the short allele of 5- HTTLPR , a serotonin transporter gene implicated in alcohol dependence risk, 55 had the smallest amygdala volumes compared to long allele and LR counterparts. 53 The authors hypothesized that smaller amygdala volumes are a result of stressful childhood experiences, as family cohesion predicted larger amygdalas, and that those who had short alleles were most vulnerable to environmental influences. 53 However, some evidence suggests that smaller amygdala volumes are the result of a developmental lag rather than a static difference between FHP and FHN individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dager and colleagues (2015) observed significantly smaller amygdala volumes in FH+ as compared to FH− individuals, which is notable given the large sample size and correction for multiple comparisons. Hill and colleagues (2013a) similarly documented significantly smaller total, right, and left amygalar volumes in the FH+ group as compared to the FH− group. Other studies have corroborated these findings (Benegal et al 2007; Hill et al, 2001); however, other groups reported no differences in amygdalar volumes between FH groups (Cservenka et al, 2015; Sjoerds et al, 2013).…”
Section: Resultsmentioning
confidence: 74%